Non-traditional Cardiovascular Risk Factors in Chronic Kidney Disease (CKD) and Haemodialysis Dependent patients - A Case Control Study - Gupta, Ratan Das; Rahman, Muhibur; Ahasan, HAM Nazmul; Alam, Md Billal; Miah, Md Titu; Kabir, Ahmedul; Das, Aparna; Mahbub, Md Shahriar; Khan, Mohammad Ashik Imran (Journal of Medicine, 2010)
Background: Compared with general population mortality rates are 10-20 times higher among patients with end stage renal disease, with 50% of this excess burden being attributable to cardiovascular disease. This excess risk is not entirely explained by elevation of traditional risk factors. Elevation of several Non-traditional risk factors associated with an increased risk for cardiovascular disease in CKD and haemodialysis dependent patients. Methods: It was a case control study which included total 96 subjects, 48 were non-dialysis CKD patients, 22 Heamodialysis dependent patients and 26 healthy controls. Non-traditional risk factors homocysteine, fibrinogen, CRP, factor VII activity and haemoglobin estimated and compared with normal control population. Results: The study revealed that homocysteine , fibrinogen , CRP, factor VII significantly increased and haemoglobin was significantly low in both non-dialysis CKD and haemodialysis dependent patients in comparison to control group. Mean homocysteine 15.38, 27.30, 23.76 μmol/L in control, non-dialysis CKD and haemodialysis dependent patient respectively. Fibrinogen in control , non-dialysis CKD and haemodialysis dependent patient were 180.25 , 264.10 , 259.59 mg/dl respectively. CRP level in control, non-dialysis CKD and haemodialysis dependent patient were 3.90, 52.59, 17.31 mg/L respectively. Factor VII activity in control was 94.18%, whereas in non-dialysis CKD it was 103.97%, and 106.18 % in haemodialysis dependent patient. haemoglobin was 13.85 gm/dl in control , but in nondialysis CKD it was 8.08 gm/dl, and in haemodialysis dependent patients 9.46 gm/dl .cardiovascular disease in nondialysis CKD 54.56% and haemodialysis dependent patients 59.4% Conclusion: Haemoglobin is low and levels of homocysteine, fibrinogen, CRP, factor-VII activity are increased among the patients with CKD and haemodialysis dependent patients. Key words: Non-traditional; Cardiovascular; Chronic Kidney Disease DOI: 10.3329/jom.v11i2.5450 J MEDICINE 2010; 11 : 108-114